PRAKTEK MANAJEMEN LABA PADA PERUSAHAAN GO PUBLIC DI INDONESIA DENGAN PENDEKATAN LONG TERM DAN SHORT TERM ACCRUAL MODEL (Studi Empiris Pada Jakarta Islamic Index ( JII ) Periode 2004 â2010 ) - Purbasari, Heppy (Universitas Muhammadiyah Surakarta, 2013)
In the recent time, earning management is still in the controversial area, earningÂ management practice viewed based on two different perspectives, first perspectives believed that itÂ was a mal practices (negatives), however, the other perspectives tend to said it should did byÂ management (positives). The aim of this study is to analyze the differentiation of the earningÂ management practices on the company listed in Jakarta Islamic Index based on long and short termdiscretionary accrual approach. The result based on Wilcoxon signed rank test shown there is asignificant differentiation between long and short term discretionary accrual. Thus, in the earningÂ management practices that found in the company listed on JII since 2004 â 2010, managementtend to increased earning on the long term discretionary accrual model (average 0,1868196)Â rather than short term discretionary accrual model (average -0,5880015).